2002
DOI: 10.1080/10284150290020754
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Prenatal Lipids Affect Myelin Gene Expression in Postnatal Undernourished Rats

Abstract: The effects on myelin gene expression of prenatal diets with a different lipid content and fatty acid composition were investigated in undernourished pups. Three groups of rats were fed ad libitum during gestation diets containing either 10% of margarine or 10% of microbial lipids or a standard diet containing 3.5% of lipids. After birth, all groups were switched to a reduced intake (60%) of the standard diet. A control group received ad libitum, the standard diet during pregnancy and throughout lactation. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The importance of nutrition in myelin development during early life is well established (6,34,(52)(53)(54). It can be argued that, in this model, disruption in myelin formation could be attributed, in part, to poor nutrition.…”
Section: Myelination In Hypoxiamentioning
confidence: 87%
“…The importance of nutrition in myelin development during early life is well established (6,34,(52)(53)(54). It can be argued that, in this model, disruption in myelin formation could be attributed, in part, to poor nutrition.…”
Section: Myelination In Hypoxiamentioning
confidence: 87%
“…Diet in particular has been studied in the context of developmental myelination, where polyunsaturated fatty acids (PUFAs) have been linked to increased myelin gene expression and protection against white matter injury, with PUFA administration during maternal gestation leading to accelerated myelination and early development of behavioral reflexes (Confaloni et al, 1993;Gozzo et al, 1982;Salvati et al, 1996;Salvati et al, 2002;Tian et al, 2011;Tuzun et al, 2012). PUFAs are integral components of cell membranes including myelin membranes (Yurlova et al, 2011).…”
Section: Common Effectors? the Potential For Intersecting Mechanisms mentioning
confidence: 99%
“…In agreement, recent studies in liver cells have shown that aging or dietary fats cause malfunction in the UPS (Tomaru et al, 2012) or chaperone-mediated autophagy (Rodriguez-Navarro et al, 2012). How dietary fats affect protein degradative mechanisms in peripheral nerves is unknown, however exogenous lipids are critical for myelination (Salvati et al, 2002). For translational consideration, these studies also revealed that analyses of steady–state protein levels are not necessarily a good indication of pathway activity, certainly not in the case of the chaperone and the autophagy-lysosomal systems.…”
Section: Calorie Restriction Delays Aging-associated Peripheral Nervementioning
confidence: 99%